Protective effects of desipramine on alveolar bone in experimental periodontitis - Branco-de-Almeida, Luciana S.; Franco, Gilson C. N.; Castro, Myrella L.; Vieira, Mayana S.; Galvao-Moreira, Leonardo; Cortelli, Sheila C.; Anbinder, Ana L. [UNESP]; Kawai, Toshihisa; Rosalen, Pedro L. (Wiley-Blackwell, 2020)
Background Desipramine is a tricyclic antidepressant with immune-modulatory activity, whose effects on ligature-induced periodontitis are yet to be investigated. Hence, its actions on alveolar bone resorption, gingival collagen content and key inflammatory mediators were herewith analyzed. Methods A total of 60 male Wistar rats were randomly assigned into three groups: 1) control: rats without ligature treated with vehicle (saline); 2) ligature: rats with ligature-induced periodontitis treated with vehicle; 3) ligature + desipramine: rats with ligature-induced periodontitis treated with desipramine (20 mg/kg/d in vehicle). Mandibles and gingival tissues were collected 3 or 15 days after ligature insertion (or no ligature insertion for controls) and treatments. Alveolar bone resorption and gingival collagen fibers were histologically analyzed using either HE or picrosirius red staining. Gingival mRNA expressions of interleukin (IL)-1 beta, inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, matrix metalloproteinase (MMP)-9 and tissue inhibitor of metalloproteinase (TIMP)-1 were obtained through reverse transcription polymerase chain reaction. MMP-9 activity was analyzed by zymography. Results Alveolar bone loss was significantly reduced in the ligature + desipramine group (P < 0.05), whereas gingival collagen degradation was like the ligature group (P > 0.05). Desipramine administration downregulated mRNA expressions of IL-1 beta, iNOS, COX-2, and TIMP-1 when compared to vehicle alone in the ligature group (P < 0.05). MMP-9 expression and MMP-9/TIMP-1 ratio were similar among rats with ligature-induced periodontitis (P > 0.05); however, MMP-9 activity was lower in the group treated with desipramine (P < 0.05). Conclusion Desipramine administration reduced alveolar bone loss as histologically observed, and modulated key bone remodeling and inflammatory mediators in rats with ligature-induced periodontitis.
Keywords: bone resorption; collagen; desipramine; inflammation; periodontal diseases